Tomato production under protected conditions with foliar applications of metal nanoparticles - Olivarez-Rodríguez, Olivarez-Rodríguez; Apáez-Barrios, Patricio; Raya-Montaño, Yurixhi Atenea; Apáez-Barrios, Maricela (Revista Mexicana de Ciencias Agrícolas, 2024)
Tomato (Solanum lycopersicum, L.) is the most important vegetable in the world in terms of production volumes, which will have to continue to increase to meet future consumption needs. In this regard, the use of nanotechnology could make the supply of nutrients to plants more efficient and improve and increase agricultural production. The objective of the study was to determine the effect of foliar application of Zn, Cu, and Fe nanoparticles on tomato production and quality. In 2021, a Roma-type tomato crop was established under protected agriculture. The treatments consisted of the individual and combined foliar application of nanoparticles of Zn, Fe, Cu, Zn+Fe, Zn+Cu, Fe+Cu, Zn+Fe+Cu, plus a control without application. It was found that the individual application of the nanoparticles did not improve tomato production, however, the combined supply increased the yield. The highest production was recorded with Zu+Fe+Cu, which was 66% higher than the control plants, with this treatment the lycopene content also doubled (2.23 mg g-1 dry matter). The nanoparticles increased the nutrient content within the maximum limit allowed for consumption. Therefore, the application of micronutrient nanoparticles supplied in combination is a viable alternative to improve tomato yield and quality.